Flow [videorecording (DVD)] - Zilbalodis, Gints, 1994-; Zilbalodis, Gints, 1994-; Zilbalodis, Gints, 1994-; Kaža, Matīss, 1995-; Dyens, Ron, 1970-; Zal̦upe, Rihards, 1983-; Silly-Pélissier, Léo (Criterion collection, 2025)
After a catastrophic flood destroys its home, a solitary cat takes refuge on a boat shared with a capybara, a lemur, a bird, and a dog. Forced to overcome their differences, the animals must cooperate to navigate the flooded world in search of safety. Their survival depends on trust, courage, and resourcefulness in the face of an uncertain future.